Who gets a mammogram amongst European women aged 50-69 years and why are there such large differences across European countries? - Ansgar Wübker (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2011)
On the basis of the Survey of Health, Ageing, and Retirement (SHARE), we analyse the determinants of who engages in mammography screening focusing on European women aged 50-69 years. A special emphasis is put on the measurement error of subjective life expectancy and on the measurement and impact of physician quality. Our main findings are that physician quality, better education, having a partner, younger age and better health are associated with higher rates of receipt. The impact of subjective life-expectancy on screening decision substantially increases after taking measurement error into account. In light of the enormous differences in mammography screening rates between the European countries that can be detected even if several individual characteristics are taken into account, we explore in a second step the causes of these screening differences using newly available data from the SHARELIFE. The results reveal that in countries with low screening rates (e.g. Denmark, Greece and Poland) many reasons (financial restrictions, time costs, access barriers, lack of information, not usual and low perceived benefits of screening) are significant predictors of not receiving a mammogram. In contrast in countries with high screening rates such as the Netherlands only beliefs regarding the benefits of mammograms (Not considered to be necessary) and the cause Not usual to get this type of care seem to be important screening barriers.
Keywords: C26; I11; I18; 330